A. R. Luria and Scenario Management - Bekoeva, D (KnE Life Sciences, 2018)
On the basis of the analysis of A. R. Luria’s biography, the article discusses the issue of leadership thinking in science and life scenario management. The article shows that the main parameter of the scenario thinking of successful people when resolving unexpectedly occurring problems with a great measure of uncertainty is the vision of purpose and future perspectives. The main conclusion lies in the fact that in teaching university students, life-scenario development must be started with the purpose vision and technologies of mental imaging. Managing your leadership capital, possessing the ability to understand new things, applying them into the new life scenario in conditions changed are activated by purpose vision. Keywords: leader, biography, teaching, life scenario, self-management, scenario management